Avaliação do efeito da (+)-catequina em células estreladas hepáticas - Moraes, Cristina Machado Bragança de (2012)
This study aimed to evaluate the antiproliferative effect of catechin, as if it has the capacity to reverse the phenotype of GRX cells, and the mechanisms involved in these outcomes. We evaluated the growth and cell proliferation in hepatic stellate cell line activated, the GRX, which were treated with catechin, and cocoa extract, and between the possible mechanisms involved in cell growth was assessed by cell necrosis release of lactate dehydrogenase, apoptosis, by expression of caspase 3 and PARP, as well as the expression of autogagia LC3. The cell cycle was measured by the expression of p53 and p27, as well as inflammatory pathways of IL-6 and COX-2 were assessed by RTPCR Real-time quantification and fibrogenic factor TGF-β. The phenotypic reversion was determined by the presence of fat in the cells with Oil-Red, as well as the expression of PPAR γ, an important regulator of adipogenesis. We evaluated the total collagen and collagen type 1 cells after treatment. It can be seen that both catechin as the cocoa extract decreased the cell growth and proliferation and that this decrease was not due to necrosis and even the activation of apoptosis and autophagy. Catechin induced cell cycle arrest by the reduction of p53 and p27, as well as decreasing the expression of inflammatory proteins such as IL-6 and COX-2 and TGF-β factor fibrogenic. The phenotypic reversion, can observe the presence of fat droplets in the cells after treatment with catechin and cocoa extract, as well as a reduction in collagen type I and an increase in expression following treatment with PPAR γ catechin. In conclusion, catechin decreases cell growth GRX, probably anti-inflammatory activity and for stopping the cell cycle. Catechin decreases the synthesis of TGF-β by cells demonstrating the potential antifibrotic effect. It also presents the property to revert the activated phenotype of GRX cells to a quiescent state and this mechanism may be via activation of PPAR gamma metabolic pathway.